Activities of the summer party of the 46th Japanese Antarctic Research Expedition in 2004-2005 - Kouji Matsubara (National Institute of Polar Research, 2006)
The summer activities of the 2004-2005 austral summer of the 46th Japanese Antarctic Research Expedition (JARE-46) are reported. JARE-46 consisted of 62 members including 25 members of the summer party and 37 members of the wintering party. An additional, three summer members companied the expedition as observers. The Antarctic research vessel (icebreaker) "Shirase" reached the pack ice edge near Lützow-Holm Bay on 14th December 2004 and anchored at Syowa Station on 21st December. A total of 980.8 t of cargo was transported including light oil transported by pipe and freight transported by snow vehicles and by helicopter. Facilities at Syowa Station were constructed. Summer research programs included atmospheric observations and geodesy at Syowa Station, and geological and biological field surveys in ice-free areas along Lützow-Holm Bay, the Prince Olav Coast and West Enderby Land. All of the summer party left Syowa Station on 9th February and headed to Sydney, Australia. Oceanography, marine biological observations and marine geomagnetism were carried out on board en route to and from Syowa Station. Members of the summer party of JARE-46 returned to Narita on 28th March 2005. Personnel were transported to Dome Fuji Station by airplane via the Russian Antarctic Station, Novolazarevskaya.